Networks : an introduction - Newman, M. E. J. (Mark E. J.) (Oxford : Oxford University Press, 2010)
This book brings together advances in mathematics, physics computer science, biology & social network analysis to present a comprehensive picture of the scientific study of networks. The book includes discussion of computer networks, social networks biological networks, & others, & an introduction to the mathematics of network theory.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Computer networks -- Mathematics; Social networks -- Mathematics; System analysis; Algorithms